A modified nylon-based composite material and its preparation method and application
By growing silica aerogel in situ on glass fibers and preparing modified glass fibers, the problem of uneven distribution of glass fibers in existing MC nylon wheels is solved, the mechanical properties and dimensional stability of nylon-based composite materials are improved, and better interface bonding and thermal stability are achieved.
Patent Information
- Application Number
- CN202410806873.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-06-21
AI Technical Summary
After the existing MC nylon wheels are added with glass fibers, the melt flowability and uneven fiber distribution lead to unstable mechanical properties and poor dimensional stability.
The modified glass fibers were prepared by growing silica aerogel-modified in-situ on the surface, and the modified glass fibers were prepared by sol preparation, coating treatment, gel treatment and supercritical carbon dioxide drying, so as to improve their dispersion in nylon substrates.
Through the use of modified glass fibers, the mechanical properties and dimensional stability of nylon-based composite materials are improved, the interface bond strength between the fiber and the nylon matrix is enhanced, the material's fracture resistance and toughness are improved, and thermal stability is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a modified nylon-based composite material and a preparation method and application thereof. Background Art
[0002] As a new type of engineering plastic, MC nylon is gradually being considered for use in the manufacture of elevator transmission wheels due to its light weight, high strength, and self-lubricating properties, in order to solve the problems of traditional cast iron wheels, such as heavy weight, difficult processing, and high cost.
[0003] However, compared with conventional technical materials, MC nylon wheels have the disadvantages of low modulus, poor dimensional stability and heat resistance. Therefore, glass fiber or other fiber fillers are usually added to the nylon substrate in the prior art to improve its dimensional stability. However, the addition of glass fiber will also bring other problems. Conventional MC nylon wheels are prepared by a monomer casting method. Glass fiber and monomer raw materials are added to the mold in a molten state, and a condensation reaction occurs under the catalysis of a catalyst to finally obtain a nylon wheel. Due to the presence of glass fiber, the fluidity of the melt is poor, and due to the density difference between the materials, the glass fiber is unevenly distributed in the melt, which will eventually lead to unstable mechanical properties of the nylon wheel. The uneven distribution of glass fiber will also lead to poor dimensional stability of the nylon wheel.
[0004] In view of this, how to improve the dispersion of glass fibers in nylon composites, thereby improving the mechanical properties and dimensional stability of nylon-based composites has become one of the technical problems that need to be solved urgently. Summary of the invention
[0005] In view of this, the present invention proposes a modified nylon-based composite material and a preparation method and application thereof.
[0006] The technical solution of the present invention is achieved in this way. The present invention provides a modified nylon-based composite material, the raw materials of which are calculated by weight:
[0007]
[0008] The modified glass fiber is a glass fiber with silica aerogel in-situ grown on the surface.
[0009] In some embodiments, the method for preparing the modified glass fiber comprises:
[0010] Sol preparation: tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0011] Coating treatment: immerse the glass fiber in the sol solution and stir for 1-5 minutes;
[0012] Gel treatment: Take the glass fiber out of the sol solution and transfer it to a water bath at 25-40°C, keep it warm and let it stand for 12-24 hours to obtain a glass fiber with gelled surface;
[0013] Drying treatment: The surface gelled glass fiber is dried with supercritical carbon dioxide to obtain modified glass fiber.
[0014] In some embodiments, the glass fibers have an average length of 1-2 mm and an average diameter of 3-10 μm.
[0015] In some embodiments, after the drying treatment, the method further comprises: coupling treatment: soaking the modified glass fiber obtained by drying in a silane coupling agent KH-550 for 5-10 seconds, and drying after soaking to obtain the modified glass fiber.
[0016] In some embodiments, the catalyst is hexamethylene diisocyanate.
[0017] In some embodiments, the stabilizer is 2,6-di-tert-butyl-p-cresol.
[0018] In some embodiments, the lubricant is ethylene bisstearamide.
[0019] In some embodiments, the compatibilizer is maleic anhydride grafted polypropylene.
[0020] In a second aspect, the present invention further provides a method for preparing a modified nylon-based composite material, comprising the following steps:
[0021] Step 1: Heat the caprolactam monomer to 70-80°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, and stir evenly;
[0022] Step 2: Pour the melt obtained in step 1 into a mold preheated to 130-150°C, add a catalyst, keep warm and vacuum dehydrate for 10-15 minutes, and stop vacuuming;
[0023] Step 3: Heat the mold to 150-160°C and keep it at this temperature for 10-20 minutes;
[0024] Step 4: demoulding after cooling, and immersing the obtained composite material in water at 100° C. for 30-60 minutes to obtain a modified nylon-based composite material.
[0025] In a third aspect, the present invention further provides an application of the modified nylon-based composite material, wherein the modified nylon-based composite material is used to prepare a rope pulley, a guide wheel or a transmission wheel.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention adopts in-situ aerogel-modified glass fiber, and a layer of nano-scale porous silica aerogel can be formed on the surface of the glass fiber. This structure greatly increases the surface area of the fiber, reduces the overall density of the glass fiber, and helps to enhance the dispersibility of the fiber in the nylon matrix. The silica aerogel layer can produce a good interface bond with the nylon matrix, and improve the interface bonding strength between the glass fiber and the nylon matrix through physical adsorption and chemical bonding. In addition, the porous structure of the aerogel layer can evenly disperse stress, reduce stress concentration points, and thus improve the fracture resistance and toughness of the material. Secondly, the aerogel has excellent thermal insulation properties, which can effectively block the transfer of heat and improve the thermal stability of the composite material. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0030] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.
[0031] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.
[0032] One embodiment of the present invention is a modified nylon-based composite material, the raw materials of which include the following components in parts by weight:
[0033]
[0034] The modified glass fiber is a glass fiber with silica aerogel in-situ grown on the surface.
[0035] Unless otherwise specified in the following embodiments, the relevant parts are all parts by weight. In one embodiment, the raw materials include:
[0036]
[0037] In one embodiment, the raw materials include:
[0038]
[0039] In one embodiment, the modified glass fiber is a glass fiber with in-situ grown silica aerogel on the surface. The glass fiber with in-situ grown silica aerogel refers to a layer of silica aerogel attached to the surface of the glass fiber formed by in-situ growth.
[0040] In one embodiment, the method for preparing the modified glass fiber comprises:
[0041] Sol preparation: tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0042] Coating treatment: immerse the glass fiber in the sol solution and stir for 1-5 minutes;
[0043] Gel treatment: Take the glass fiber out of the sol solution and transfer it to a water bath at 25-40°C, keep it warm and let it stand for 12-24 hours to obtain a glass fiber with gelled surface;
[0044] Drying treatment: The surface gelled glass fiber is dried with supercritical carbon dioxide to obtain modified glass fiber.
[0045] The precursor sol of the silica aerogel is attached to the surface of the glass fiber by stirring to form a sol film, and the sol film forms a semi-solidified gel during the gelation process, and finally an aerogel attachment layer is obtained by supercritical drying.
[0046] In one embodiment, during the preparation of the sol, a certain amount of surfactant, such as hydroxypropyl cellulose, may be added in an amount of 10% (m / v) of tetraethoxysilane to help improve the uniformity of the sol's adhesion to the glass fiber surface.
[0047] During the drying process, in a supercritical drying device, the pressure is gradually increased to a supercritical state (7.4 MPa) and the temperature is maintained at 31-40° C., and then the pressure is gradually released to obtain an aerogel.
[0048] The drying process can also be carried out in a vacuum drying oven by gradually reducing the pressure and controlling the temperature at 25-40° C. for 24-48 hours.
[0049] In some embodiments, the glass fibers have an average length of 1-2 mm and an average diameter of 3-10 μm.
[0050] With the size of the glass fiber of the above embodiment, after in-situ growth of silica aerogel on the surface, the overall density of the modified glass fiber obtained is close to that of the nylon matrix, which is more conducive to uniform distribution of the modified glass fiber in the nylon matrix.
[0051] In some embodiments, after the drying treatment, the method further includes: coupling treatment: soaking the modified glass fiber obtained by drying in a silane coupling agent KH-550 for 5-10 seconds, and drying after soaking to obtain the modified glass fiber.
[0052] The coupling treatment can effectively improve the interfacial bonding strength between the porous silica aerogel formed by in-situ growth on the glass fiber surface and the nylon substrate. At the same time, the water resistance of the silica aerogel can be improved after treatment with KH-550 coupling agent.
[0053] Example 1
[0054] This embodiment provides a rope pulley of nylon-based composite material, and its raw materials include, by weight:
[0055] 65 parts of caprolactam monomer, 25 parts of modified glass fiber, 1.2 parts of hexamethylene diisocyanate, 0.5 parts of 2,6-di-tert-butyl-p-cresol, 0.5 parts of ethylene bisstearamide, and 1.2 parts of maleic anhydride grafted polypropylene.
[0056] The preparation of modified glass fiber:
[0057] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0058] Glass fibers with an average length of 1 mm and an average diameter of 3 μm were immersed in the sol solution and stirred for 5 min;
[0059] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 40°C, and kept at this temperature for 12 hours to obtain a glass fiber with a gelled surface;
[0060] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain modified glass fiber.
[0061] Preparation of rope sheaves made of nylon-based composite materials:
[0062] Heat the caprolactam monomer to 75°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 130°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 150°C, keep warm and stand for 20 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0063] Example 2
[0064] This embodiment provides a rope pulley of nylon-based composite material, and its raw materials include, by weight:
[0065] 50 parts of caprolactam monomer, 20 parts of modified glass fiber, 0.5 parts of hexamethylene diisocyanate, 0.1 parts of 2,6-di-tert-butyl-p-cresol, 0.1 parts of ethylene bisstearamide, and 0.5 parts of maleic anhydride grafted polypropylene.
[0066] The preparation of modified glass fiber:
[0067] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0068] Glass fibers with an average length of 1 mm and an average diameter of 3 μm were immersed in the sol solution and stirred for 3 min;
[0069] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 30°C, and kept at this temperature for 20 hours to obtain a glass fiber with a gelled surface;
[0070] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain modified glass fiber.
[0071] Preparation of rope sheaves made of nylon-based composite materials:
[0072] Heat the caprolactam monomer to 70°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 135°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 10 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 155°C, keep warm and stand for 15 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0073] Example 3
[0074] This embodiment provides a rope pulley of nylon-based composite material, and its raw materials include, by weight:
[0075] 80 parts of caprolactam monomer, 30 parts of modified glass fiber, 3 parts of hexamethylene diisocyanate, 1 part of 2,6-di-tert-butyl-p-cresol, 1 part of ethylene bisstearamide, and 2 parts of maleic anhydride grafted polypropylene.
[0076] The preparation of modified glass fiber:
[0077] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0078] Glass fibers with an average length of 1 mm and an average diameter of 3 μm were immersed in the sol solution and stirred for 1 min;
[0079] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 25°C, and kept at this temperature for 24 hours to obtain a glass fiber with a gelled surface;
[0080] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain modified glass fiber.
[0081] Preparation of rope sheaves made of nylon-based composite materials:
[0082] Heat the caprolactam monomer to 80°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 150°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 160°C, keep warm and stand for 10 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 60 minutes to obtain a modified nylon-based rope wheel.
[0083] Example 4
[0084] This embodiment provides a rope pulley of nylon-based composite material, and its raw materials include, by weight:
[0085] 65 parts of caprolactam monomer, 25 parts of modified glass fiber, 1.2 parts of hexamethylene diisocyanate, 0.5 parts of 2,6-di-tert-butyl-p-cresol, 0.5 parts of ethylene bisstearamide, and 1.2 parts of maleic anhydride grafted polypropylene.
[0086] The preparation of modified glass fiber:
[0087] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0088] Glass fibers with an average length of 1 mm and an average diameter of 3 μm were immersed in the sol solution and stirred for 5 min;
[0089] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 40°C, and kept at this temperature for 12 hours to obtain a glass fiber with a gelled surface;
[0090] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain a modified glass fiber, and the modified glass fiber is immersed in a silane coupling agent KH-550 for 5 seconds, and then dried to obtain the modified glass fiber.
[0091] Preparation of rope sheaves made of nylon-based composite materials:
[0092] Heat the caprolactam monomer to 75°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 130°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 150°C, keep warm and stand for 20 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0093] Example 5
[0094] This embodiment provides a rope pulley of nylon-based composite material, and its raw materials include, by weight:
[0095] 65 parts of caprolactam monomer, 25 parts of modified glass fiber, 1.2 parts of hexamethylene diisocyanate, 0.5 parts of 2,6-di-tert-butyl-p-cresol, 0.5 parts of ethylene bisstearamide, and 1.2 parts of maleic anhydride grafted polypropylene.
[0096] The preparation of modified glass fiber:
[0097] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1, and then hydroxypropyl cellulose is added, and the mass volume ratio of hydroxypropyl cellulose to tetraethoxysilane is 1:10 (m / v), and a sol solution is obtained after mixing;
[0098] Glass fibers with an average length of 1 mm and an average diameter of 3 μm were immersed in the sol solution and stirred for 5 min;
[0099] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 40°C, and kept at this temperature for 12 hours to obtain a glass fiber with a gelled surface;
[0100] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain modified glass fiber.
[0101] Preparation of rope sheaves made of nylon-based composite materials:
[0102] Heat the caprolactam monomer to 75°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 130°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 150°C, keep warm and stand for 20 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0103] Example 6
[0104] This embodiment provides a rope pulley of nylon-based composite material, and its raw materials include, by weight:
[0105] 65 parts of caprolactam monomer, 25 parts of modified glass fiber, 1.2 parts of hexamethylene diisocyanate, 0.5 parts of 2,6-di-tert-butyl-p-cresol, 0.5 parts of ethylene bisstearamide, and 1.2 parts of maleic anhydride grafted polypropylene.
[0106] The preparation of modified glass fiber:
[0107] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1, and then hydroxypropyl cellulose is added, and the mass volume ratio of hydroxypropyl cellulose to tetraethoxysilane is 1:10 (m / v), and a sol solution is obtained after mixing;
[0108] Glass fibers with an average length of 1 mm and an average diameter of 3 μm were immersed in the sol solution and stirred for 5 min;
[0109] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 40°C, and kept at this temperature for 12 hours to obtain a glass fiber with a gelled surface;
[0110] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain a modified glass fiber, and the modified glass fiber is immersed in a silane coupling agent KH-550 for 5 seconds, and then dried to obtain the modified glass fiber.
[0111] Preparation of rope sheaves made of nylon-based composite materials:
[0112] Heat the caprolactam monomer to 75°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 130°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 150°C, keep warm and stand for 20 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0113] Example 7
[0114] This embodiment provides a rope pulley of nylon-based composite material, and its raw materials include, by weight:
[0115] 65 parts of caprolactam monomer, 25 parts of modified glass fiber, 1.2 parts of hexamethylene diisocyanate, 0.5 parts of 2,6-di-tert-butyl-p-cresol, 0.5 parts of ethylene bisstearamide, and 1.2 parts of maleic anhydride grafted polypropylene.
[0116] The preparation of modified glass fiber:
[0117] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0118] Glass fibers with an average length of 2 mm and an average diameter of 10 μm were immersed in the sol solution and stirred for 5 min;
[0119] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 40°C, and kept at this temperature for 12 hours to obtain a glass fiber with a gelled surface;
[0120] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain modified glass fiber.
[0121] Preparation of rope sheaves made of nylon-based composite materials:
[0122] Heat the caprolactam monomer to 75°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 130°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 150°C, keep warm and stand for 20 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0123] Comparative Example 1
[0124] This comparative example provides a rope pulley of a nylon-based composite material, which is different from Example 1 in that the glass fiber is not modified, and the raw materials thereof include, by weight:
[0125] 65 parts of caprolactam monomer, 25 parts of glass fiber, 1.2 parts of hexamethylene diisocyanate, 0.5 parts of 2,6-di-tert-butyl-p-cresol, 0.5 parts of ethylene bisstearamide, and 1.2 parts of maleic anhydride grafted polypropylene.
[0126] Preparation of rope sheaves made of nylon-based composite materials:
[0127] Heat the caprolactam monomer to 75°C, add glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 130°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 150°C, keep warm and stand for 20 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0128] Comparative Example 2
[0129] This comparative example provides a nylon-based composite rope pulley, which is different from Example 1 in that the glass fiber is shorter, and its raw materials include, by weight:
[0130] 65 parts of caprolactam monomer, 25 parts of modified glass fiber, 1.2 parts of hexamethylene diisocyanate, 0.5 parts of 2,6-di-tert-butyl-p-cresol, 0.5 parts of ethylene bisstearamide, and 1.2 parts of maleic anhydride grafted polypropylene.
[0131] The preparation of modified glass fiber:
[0132] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0133] Glass fibers with an average length of 0.5 mm and an average diameter of 3 μm were immersed in the sol solution and stirred for 5 min;
[0134] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 40°C, and kept at this temperature for 12 hours to obtain a glass fiber with a gelled surface;
[0135] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain modified glass fiber.
[0136] Preparation of rope sheaves made of nylon-based composite materials:
[0137] Heat the caprolactam monomer to 75°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 130°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 150°C, keep warm and stand for 20 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0138] Comparative Example 3
[0139] This comparative example provides a nylon-based composite rope pulley, which is different from Example 1 in that the glass fiber is longer, and its raw materials include, by weight:
[0140] 65 parts of caprolactam monomer, 25 parts of modified glass fiber, 1.2 parts of hexamethylene diisocyanate, 0.5 parts of 2,6-di-tert-butyl-p-cresol, 0.5 parts of ethylene bisstearamide, and 1.2 parts of maleic anhydride grafted polypropylene.
[0141] The preparation of modified glass fiber:
[0142] Tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1 to obtain a sol solution;
[0143] Glass fibers with an average length of 15 mm and an average diameter of 3 μm were immersed in the sol solution and stirred for 5 min;
[0144] The glass fiber with the sol attached to the surface is taken out from the sol solution and transferred to a water bath at 40°C, and kept at this temperature for 12 hours to obtain a glass fiber with a gelled surface;
[0145] The surface gelled glass fiber is dried by supercritical carbon dioxide to obtain modified glass fiber.
[0146] Preparation of rope sheaves made of nylon-based composite materials:
[0147] Heat the caprolactam monomer to 75°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, stir for 5 minutes, add the melt into the rope wheel mold preheated to 130°C, and add hexamethylene diisocyanate. Keep warm and vacuum dehydrate for 15 minutes, the vacuum degree is 99.8kPa, and then stop vacuuming; after returning to normal pressure, heat the mold to 150°C, keep warm and stand for 20 minutes, cool to 30°C, demould, and soak the obtained rope wheel in 100°C water for 30 minutes to obtain a modified nylon-based rope wheel.
[0148] The above-prepared embodiments and comparative examples were tested for tensile strength, flexural strength, notched impact strength, heat deformation temperature and surface quality, and the results were shown in the following table:
[0149]
[0150] It can be seen from the above data that the scheme of the embodiment of the present application has obvious improvements in tensile strength, flexural strength, notched impact strength, heat deformation temperature and surface quality. It is considered that the glass fiber modified by the surface in-situ growth of silica aerogel has obtained better dispersibility in the nylon substrate, and it can be seen from the data of Examples 4-6 that the mechanical strength and high temperature resistance can be significantly improved by further modifying the silica aerogel attachment layer on the surface; and by adding a small amount of hydroxypropyl cellulose to the sol liquid, the mechanical properties and high temperature resistance are also significantly improved. It is considered that the addition of hydroxypropyl cellulose improves the uniform adhesion effect of the precursor sol of the aerogel on the surface of the glass fiber, thereby further improving its dispersibility and the bonding performance with the nylon matrix. The modified nylon-based composite material of the present application not only improves the mechanical properties of the material, but also has a significant improvement effect on the appearance performance, and has good application prospects.
[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A modified nylon-based composite material, characterized in that: Calculated by weight, the raw materials of the modified nylon-based composite material include: The modified glass fiber is a glass fiber with silica aerogel in situ grown on the surface; the average length of the glass fiber is 1-2 mm, and the average diameter is 3-10 μm; The preparation method of the modified glass fiber comprises: Sol preparation: tetraethoxysilane, anhydrous ethanol, deionized water and hydrochloric acid are mixed in a volume ratio of 10:40:8:1, and then hydroxypropyl cellulose is added in an amount of 10% (m / v) of tetraethoxysilane to obtain a sol solution; Coating treatment: immerse the glass fiber in the sol solution and stir for 1-5 minutes; Gel treatment: Take the glass fiber out of the sol solution and transfer it to a water bath at 25-40°C, keep it warm and let it stand for 12-24 hours to obtain a glass fiber with gelled surface; Drying treatment: drying the surface gelled glass fiber with supercritical carbon dioxide to obtain modified glass fiber; Coupling treatment: soak the modified glass fiber obtained by drying in silane coupling agent KH-550 for 5-10 seconds, and then dry it to obtain the modified glass fiber.
2. The modified nylon-based composite material according to claim 1, characterized in that: The catalyst is hexamethylene diisocyanate.
3. The modified nylon-based composite material according to claim 1, characterized in that: The stabilizer is 2,6-di-tert-butyl-p-cresol.
4. The modified nylon-based composite material according to claim 1, characterized in that: The lubricant is ethylene bisstearamide.
5. The modified nylon-based composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene.
6. The method for preparing the modified nylon-based composite material according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: Heat the caprolactam monomer to 70-80°C, add the modified glass fiber, stabilizer, lubricant and compatibilizer in the melt state, and stir evenly; Step 2: Pour the melt obtained in step 1 into a mold preheated to 130-150°C, add a catalyst, keep warm and vacuum dehydrate for 10-15 minutes, and stop vacuuming; Step 3: Heat the mold to 150-160°C and keep it warm for 10-20 minutes; Step 4: demoulding after cooling, and immersing the obtained composite material in water at 100° C. for 30-60 minutes to obtain a modified nylon-based composite material.
7. The use of the modified nylon-based composite material according to any one of claims 1 to 5, characterized in that: Used for preparing rope pulleys, guide wheels or transmission wheels.
Citation Information
Patent Citations
Preparation and method of silicon dioxide aerogel composite material
CN102557577A
High-strength and low-retraction casting nylon composite material and preparation method thereof
CN103923312A